IN VITRO MICROPROPAGATION OF WITHANIA SOMNIFERA (L.) DUNAL BY DIFFERENT CONCENTRATIONS OF GROWTH REGULATORS - RADHIKA RAMACHANDRAN; DR. K. AMUTHA (International Journal of Pharma and Bio Sciences, 2013)
Withania somnifera (L.) Dunal is an important ayurvedic medicinal plant known mainly for its rejuvenating properties. In vitro micropropagation or multiplication of Withania somnifera through apical shoot proliferation by using different concentrations of growth regulators in short period. Shoots were induced from the apical meristem of Withania somnifera on Murashige and Skoog (MS) basal media supplemented with different concentrations of 6- Benzylamino purine(BAP) (0.15, 0.20 and 0.25 mg/L). Apical meristem explants showed initiation of shoots within 6 –7 days of transfer, with optimum concentration of 0.25 mg/L and it is found to be most effective for multiple shoot generation within 1–2 weeks. The generated shoots were successfully rooted on Murashige and Skoog (MS) basal medium supplemented with Indole 3-butyric acid (IBA) (optimum concentration - 1mg/L) along with activated charcoal. Rooted plants were then transferred for primary and secondary hardening and grown in green house. These hardened plants have been successfully established in soil.